Factors influencing reading among form 4 ESL students / Aiza Johari - Johari, Aiza (2007)
This study investigates the factors, particularly family factors, which influence reading among Form 4 ESL students in SMK Green Road, in Kuching, Sarawak, Malaysia. Most ESL teachers face various challenges in teaching reading as many students find it to be arduous and tedious; hence contributing to the lack of reading ability, interest and practice. Parental socioeconomic statuses (independent variables: occupation, income and academic achievement) and home reading environments (dependent variables: reading backgrounds and habits; attitude and motivation; exposure and support) were put forward as the affecting social factors. To identify these factors, questionnaires were distributed to 120 respondents. Although not fully generalisable, this study presents some interesting and helpful information. The findings revealed that in general, most students were from average home reading environments while their parents had low to average socioeconomic statuses. Though the students acknowledged the importance of reading in their daily lives, their average reading habits, attitude, motivation, exposure and support within the home domain had suggested otherwise. They mainly read for instrumental purposes while reading for pleasure seemed not to be given priority. On average, the correlation results suggested positive relationships between all variables, which were parallel to the hypotheses and other researchers’ observations. Nonetheless, parents’ occupation had negative significance values. Likewise, the regression data revealed that parental incomes were shown to be the strongest predictor towards constructive home reading environments, followed by parental academic qualifications. Notably, parental occupations also had the lowest ability to provide better home reading environments, hence refuting the hypotheses and findings in other studies. These outcomes may occur due to the low to average socioeconomic backgrounds of the majority of the students. As an implication, it is vital for students to improve their reading perceptions, abilities and practices to achieve personal, societal and national progress. On a final note, parents’ early and continuous efforts to be involved in their children’s literacy events in an out-of-school context are believed to be more powerful than socioeconomic statuses.